Study on Pull-Up Behavior of Double Fold Anchor with Field Full Scale Test - Hendrawan, Agus J.; Harianto, Tri; Djamaluddin, A. R.; Muhiddin, Ahmad B. (Civil Engineering Journal, 2024)
Several studies have been conducted on the use of anchors, including numerical analysis, experimental testing, and field-scale testing. These studies have provided insights into anchor behavior in terms of pull-up capacity and soil failure models under tensile loading. Specifically, for the use of anchors in cohesive or soft soils, it is possible to innovate by using anchor elements with various dimensional or surface area changes. This research aims to design anchors for cohesive soils that can be easily applied in the field and have high tensile capacity, determine the pull-up capacity of double-fold type ground anchors, and analyze the effect of the depth of double-fold anchors. The results of pullout and tensile capacity testing on double-fold anchors showed significant variations at each test location. At the first location, Sungai Kariango, high tensile capacity occurred at relatively shallow embedment depths, influenced by the type and bearing capacity of the soil at the test site. At the second location, although the soil was relatively soft, the tensile capacity was similar to the first location but with deeper embedment depths. At the third location, the consistency of soil type and soil strength at the two test points resulted in similar tensile capacities. This indicates that the type and strength, or bearing capacity, of the soil at the test site, as depicted by cone resistance parameters (qc), significantly affect the tensile capacity of the anchor. The better the soil strength and bearing capacity at the test site, the greater the tensile capacity of the anchor that can be achieved. A deep understanding of soil characteristics through CPT is essential in determining the design and embedment depth of anchors to achieve optimal tensile capacity. Through this research, it is expected to obtain optimal tensile capacity results for anchors and develop a double-fold type ground anchor model that is easy to install in the field, suitable for various structures with high tensile loads, and susceptible to uplift in soft soil layers. Doi: 10.28991/CEJ-2024-010-12-012 Full Text: PDF